2021
DOI: 10.1007/s00417-021-05200-5
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular epidermal growth factor concentration, axial length, and high axial myopia

Abstract: Purpose Various molecules such as dopamine have been found to be associated with axial elongation in experimental studies. Here, we examined whether intraocular EGF is associated with axial length in myopic patients. Methods The hospital-based investigation included patients of European descent without optic nerve, retinal, or macular diseases except for myopic maculopathy. Using aqueous humor samples collected during surgery, the EGF concentration was exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…28 Jonas et al found that the intraocular amount of EGF is higher in highly myopic eyes than in non-highly myopic eyes, indicating a close association between the EGF family and myopia. 29 In conclusion, measuring AREG in tears could serve as an important surrogate marker to probe myopia mechanisms. Further studies with larger sample sizes and investigating the association between AREG and high myopia will validate these findings.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…28 Jonas et al found that the intraocular amount of EGF is higher in highly myopic eyes than in non-highly myopic eyes, indicating a close association between the EGF family and myopia. 29 In conclusion, measuring AREG in tears could serve as an important surrogate marker to probe myopia mechanisms. Further studies with larger sample sizes and investigating the association between AREG and high myopia will validate these findings.…”
Section: Discussionmentioning
confidence: 96%
“…A genome‐wide association study found that the AREG SNP (rs12511037) was associated with increased AL, indicating that AREG is etiologically relevant for ocular traits 28 . Jonas et al found that the intraocular amount of EGF is higher in highly myopic eyes than in non‐highly myopic eyes, indicating a close association between the EGF family and myopia 29 . In conclusion, measuring AREG in tears could serve as an important surrogate marker to probe myopia mechanisms.…”
Section: Discussionmentioning
confidence: 97%
“…These observations led to the question whether the intraocular application of an antibody to the EGF receptor could clinically be helpful to prevent further axial elongation in adult patients with pathologic myopia 1 4 . The notion of EGF being involved in the process of axial elongation has been supported by a recent small case series study in which the intraocular concentration of EGF was higher in the eyes of highly myopic patients than in non-highly myopic eyes 9 .…”
Section: Introductionmentioning
confidence: 95%
“…Eyes were classified into short and long axial lengths, with a cut-off value of 27.0 mm. This specific cutoff value was chosen as it aligns with the commonly used definition of high myopia [10,[17][18][19].…”
Section: Definitionsmentioning
confidence: 99%